The Significance of Desert-Based Distributive Justice to People Well-Being - Marzuki, Peter Mahmud (Universitas Airlangga, 2025)
The objective of this writing is to identify the philosophical basis for the government to enact law that creates people well-being. The background of this essay is to grasp the philosophical basis for the government to make law that is appropriate to create people well-being. Since this essay is a legal essay, the method used in this essay is legal research that employs historical approach and conceptual approach. Having analyzed the research materials, from this research, it is found that philosophical basis shared by governments of developed countries to enact law that creates people well-being notwithstanding under the guidance of distributive justice is either contemporary libertarian or contemporary egalitarian. It is concluded that the contemporary libertarian philosophy leads to inequity and the contemporary egalitarian brings about equality without considering desert. This essay gives an alternative philosophical basis for governments to impose policy in creating people well-being. This essay recommends that governments of developing countries to adopt desert-based distributive justice philosophy as the basis for enacting law that creates people well-being.